2002
DOI: 10.1086/340365
|View full text |Cite
|
Sign up to set email alerts
|

Differing Influences of Virus Burden and Immune Activation on Disease Severity in Secondary Dengue‐3 Virus Infections

Abstract: Dengue hemorrhagic fever (DHF), the most severe form of illness following infection with a dengue virus, is characterized by plasma leakage, thrombocytopenia, and hepatic inflammation. The interrelationships among virus burden, immune activation, and development of DHF were examined in 54 children with secondary dengue-3 virus infections participating in a prospective, hospital-based study. DHF was associated with higher mean plasma viremia early in illness and earlier peak plasma interferon-gamma levels. Maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
379
4
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(415 citation statements)
references
References 54 publications
29
379
4
3
Order By: Relevance
“…Several studies have demonstrated greater viral loads in patients with DHF compared to those with DF, suggesting that direct viral effects, or the magnitude of the host response to the virus, may be critical in determining disease severity (29,45). Dengue virus has been shown to infect endothelial cells in vitro (5).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated greater viral loads in patients with DHF compared to those with DF, suggesting that direct viral effects, or the magnitude of the host response to the virus, may be critical in determining disease severity (29,45). Dengue virus has been shown to infect endothelial cells in vitro (5).…”
Section: Resultsmentioning
confidence: 99%
“…Serum levels of sST2 protein were found to be elevated at the end of the febrile stage of the disease, reaching a peak between fever days −1 and 0 followed by a decrease of the levels to normal values in convalescence. The viremia tendency is to rapidly decrease at late febrile stage of the disease through defervescence [16]. The levels of sST2 tend to increase at late febrile stage and at defervescence.…”
Section: Discussionmentioning
confidence: 96%
“…Cross reactivity also generates a dysfunctional T cell response that results in suboptimal clearance of the virus and an uncontrolled production of soluble mediators [9]. Elevated circulating levels of both type 1 (Th1) and type 2 (Th2) cytokines and various chemokines including gamma interferon (IFN-γ), tumor necrosis factor alpha (TNF-α), interleukin (IL)-1beta (IL-1β), IL-6, IL-10, IL-13, IL-8, macrophage chemoattractant protein-1 (MCP-1), and macrophage inflammatory protein 1 beta (MIP-1β) have been detected in dengue infected patients [10][11][12][13][14][15][16][17][18], and the kinetics and persistence of some of these mediators seem to be related to the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…73 In addition it is known that increased IL-10 levels correlate to reduced levels of platelets and reduced platelet function. 74 This phenomenon could, in part, contribute to the development of the bleeding complications observed in severe disease.…”
Section: Cytokinesmentioning
confidence: 99%
“…Each of the DEN virus serotypes is capable of causing severe dengue and early viral burdens in the course of illness are associated with severe disease. 74,82,115 Oscillations in the prevalence of each serotype are common in endemic settings. Typically, one serotype is dominant for a period of 2-4 years, after which it declines in prevalence as a different serotype(s) emerges to replace it.…”
Section: Virus Epidemiology and Virulencementioning
confidence: 99%